Ser289 phosphorylation activates both DAPK1 and DAPK2 but in response to different intracellular signaling pathways - Shiloh, Ruth (Cell Cycle, 2019)
DAPK1 and DAPK2 are calmodulin (CaM)-regulated protein kinases that share a high degree of homology in their catalytic and CaM regulatory domains. Both kinases function as tumor suppressors, and both have been implicated in autophagy regulation. Over the years, common regulatory mechanisms for the two kinases as well as kinase-specific ones have been identified. In a recent work, we revealed that DAPK2 is phosphorylated on Ser289 by the metabolic sensor AMPK, and that this phosphorylation enhances DAPK2 catalytic activity. Notably, Ser289 is conserved between DAPK1 and DAPK2, and was previously found to be phosphorylated in DAPK1 by RSK. Intriguingly, Ser289 phosphorylation was conversely reported to inhibit the pro-apoptotic activity of DAPK1 in cells. However, as the direct effect of this phosphorylation on DAPK1 catalytic activity was not tested, indirect effects were not excluded. Here, we compared Ser289 phosphorylation of the two kinases in the same cells and found that the intracellular signaling pathways that lead to Ser289 phosphorylation are mutually-exclusive and different for each kinase. In addition, we found that Ser289 phosphorylation in fact enhances DAPK1 catalytic activity, similar to the effect on DAPK2. Thus, Ser289 phosphorylation activates both DAPK1 and DAPK2, but in response to different intracellular signaling pathways.